46th AIAA/ASME/ASCE/AHS/ASC Structures, Structural Dynamics and Materials Conference 2005
DOI: 10.2514/6.2005-1932
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Design of Stiffened Panels With Substiffeners

Abstract: The capability of the computer program PANDA2 to generate minimum-weight designs of stiffened panels and cylindrical shells is enhanced to permit the adding of substiffeners with rectangular cross sections between adjacent major stringers and rings. As a result many new buckling margins exist that govern buckling over various domains and subdomains of the doubly stiffened panel or shell. These generally influence the evolution of the design during optimization cycles. The substiffeners may be stringers and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Considering static strength, Bushnell and Rankin [10] demonstrated that including small substiffeners between the conventional primary stiffeners can, 'not only lead to an increased buckling resistance, but more importantly to a much more robust optimum in terms of stiffener pitch'. Murphy et al [3] experimentally and computationally examined plate substiffening, demonstrating potential combined performance gains for both initial plate buckling and panel post-buckling collapse.…”
Section: Panel Sub-stiffeningmentioning
confidence: 99%
“…Considering static strength, Bushnell and Rankin [10] demonstrated that including small substiffeners between the conventional primary stiffeners can, 'not only lead to an increased buckling resistance, but more importantly to a much more robust optimum in terms of stiffener pitch'. Murphy et al [3] experimentally and computationally examined plate substiffening, demonstrating potential combined performance gains for both initial plate buckling and panel post-buckling collapse.…”
Section: Panel Sub-stiffeningmentioning
confidence: 99%
“…What is more, Bushnell and Rankin [3] demonstrated that including small sub-stiffeners between the conventional primary stiffeners 'can not only lead to an increased buckling resistance, but more importantly to a much more robust optimum in terms of stiffener pitch'. Additionally, the damage tolerance characteristics of stiffener panel structures may be improved by the addition of plate element features designed to retard fatigue crack growth [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Considering static strength, numerous plate [9][10][11]18 and panel studies [12][13][14][15][16][17][19][20][21] have demonstrated that non-uniform skin thickness can be used to tailor local stability behaviour. Quinn et al 14 experimentally and computationally demonstrates that the introduction of prismatic unflanged blade sub-stiffeners within panel skin bays (see Figure 1) can significantly modify initial stability behaviour and improve both the initial buckling, and post buckling collapse performance, thus using sub-stiffeners as panel "buckling containment features".…”
Section: Buckling Containment Featuresmentioning
confidence: 99%